KINERJA BAHAN ISOLASI CAMPURAN POLIMER EPOKSIPOLISILOKSAN DENGAN PENGISI ABU SEKAM PADI SEBAGAI MATERIAL ISOLATOR TEGANGAN TINGGI DI DAERAH BERIKLIM TROPIS - , Arif Jaya, ST.,MT.; , Prof. Dr. Ir. Hamzah Berahim, M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Epoxy resin is a thermosetting polymeric material. This material is very good for application of high or extra high voltage outdoor insulator in electrical power system. Epoxy resin polymeric insulating material has several advantages, i.e. high dielectric strength, light weight, high mechanical strength, easy to blend with additive, and easy maintenance if compared with that of porcelain and glass outdoor insulators which are commonly used especially in Indonesia. However, epoxy resin material has several disadvantage, i.e. has hydrophilic property, very sensitive in the environment with high temperature, humidity, and intensity of ultraviolet radiation which will cause decreases of epoxy resin performance. Such environment is commonly seen in tropical climate area in Indonesia. The study towards improving the performance of epoxy resin polymeric insulating material has been carried out, in order to obtain EP-RHA polymeric insulating material which is the new name proposed by researcher. EP-RHA polymeric insulating material was made in room temperature vulcanization with material composition: Diglycidyl Ether of Bisphenol A (DGEBA), Meta Phenylene Diamine (MPDA) as hardener with stochiometric value of unity, and 325 mesh Rice Husk Ash (RHA) filler mixed with Polysiloxane (SiR) with 10% (RTVEP1), 20%(RTVEP2), 30%(RTVEP3), 40%(RTVEP4), and 50%(RTVEP5) variation. The usage of polysiloxane and RHA as filler is expected to provide hydrophobic property and physical strength in epoxy resin polymeric insulating material against tropical climate effect. The research was conducted in Yogyakarta, a city in Indonesia that has typical tropical climate. The experiment was carried out by two methods: 1) the natural aging was installed with natural tropical climate exposure which was conducted at Electrical Engineering and Information Technology of Gadjah Mada University building, Yogyakarta, Indonesia. EP-RHA Polymeric insulating material test samples were placed outdoor for 52 weeks, and tested their performances every 2 weeks